Psychometric Properties of The Emotion Regulation Questionnaire for Children and Adolescents (ERQ-CA) Indonesian Version - Michelle Brigitta Shanny; Afra Hafny Noer; Lucia Voni Pebriani (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Emotion regulation refers to the process of how one's emotions are formed and how individuals express these emotions. Research on measuring emotion regulation strategies is still focused on managing everyday problems, and there is no measurement of emotion regulation for children and adolescents in Indonesia that can be used. Therefore, valid and reliable measurements are needed. The Emotion Regulation Questionnaire for Children and Adolescents (ERQ-CA) is a standard measurement instrument developed by Gullone and Taffe from the adult version to the child and adolescent version to measure the difference in the use of emotional regulation strategies. This study was conducted to evaluate the psychometric properties of the adapted ERQ-CA instrument for Indonesian children and adolescents. Data were collected with a convenience sampling technique. Ten items were administered to 140 children and adolescents between 12 and 18 years of age, of whom 69.3% were female and 35.7% were in the first year of high school. ERQ-CA uses a 5 point likert scale consisting of two dimensions: cognitive reappraisal and expressive suppression. The results of CFA showed that 9 of 10 ERQ-CA items showed a good goodness of fit model (CFI = .970; GFI = .846; SRMR = .024; NFI = .962). The ERQ-CA instrument had good internal consistency reliability with Cronbach’s alpha ranging from 0.45 to 0.98, and acceptable test-retest reliability with the item discrimination all greater than 0.22. It can be concluded that the Indonesian version of the ERQ-CA has good psychometric properties, so that it can be used to measure the emotion regulation strategies of children and adolescents in Indonesia.